Solve for y 4^(-y)=64

Math
4-y=64
Create equivalent expressions in the equation that all have equal bases.
4-y=43
Since the bases are the same, then two expressions are only equal if the exponents are also equal.
-y=3
Multiply each term in -y=3 by -1
Tap for more steps…
Multiply each term in -y=3 by -1.
(-y)⋅-1=3⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=3⋅-1
Multiply y by 1.
y=3⋅-1
y=3⋅-1
Multiply 3 by -1.
y=-3
y=-3
Solve for y 4^(-y)=64

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top